The Expression of Value Internalization among the Grieving Primary School Children - Butvilas, Tomas (Acta Paedagogica Vilnensia, 2005)
Within this article we emphasize children’s social-moral behavior as the basis of their socialization expression. The diagnostic research has shown some behavioral peculiarities on the level of internalized values of those primary school children, who have experienced the loss in the family. At the most of the times the identification processes for the grieving children are laden, and they are often linked to internalize those values that are not acceptable or preferable to the society they are living in. Also we have identified that most of the socialization researches do not pay much of attention to the grieving children’s situation. Thus we tried to reveal some behavioural peculiarities of the grieving primary school children towards their gender and experienced loss. The data of the research has shown that girls, who have experienced loss in the family, could be characterized as less respectful to others, peaceful, sensible, and self-controlled than other girls or boys of the same age. Besides among the boys, who have faced the loss of a loving one, such the internalized values as sharing with others, initiation, and self-sufficiency are non-predominant. It was stated that grieving children’s social-moral behavior according to some internalized values are less stable than those, who did not experience the loss. As the matter of fact, the research data has shown that the loss experience in the family affects children’s social-moral behavior and their further relations with others (the meaningful statistic disparities were set as well).